Maintenance in gastric cancer: New life for an old issue?. (April 2021) - Roviello, Giandomenico; Rodriquenz, Maria Grazia; Aprile, Giuseppe; D'Angelo, Alberto; Roviello, Franco; Nobili, Stefania; Mini, Enrico; Sarno, Italo; Polom, Karol
Highlights: Maintenance therapy is a strategy that may strengthen results of induction therapy. Extending survival and preserving the quality of life (QoL) with less toxicity is the goal of Maintenance therapy. No established role for maintenance therapy following first-line chemotherapy for advanced gastric cancer (GC). New issues to optimize maintenance therapies and guide a personalized approach in daily clinical practice for this setting. Abstract: The interest in maintenance therapy for patients with advanced cancers has been rapidly growing. Maintenance therapy is a useful strategy that may strengthen results of induction therapy thus extending survival and preserving the quality of life (QoL) with less toxicity. Maintenance also represents a suitable setting to investigate novel agents. The value of maintenance therapy after first-line chemotherapy has been well established in several solid tumours, such as colorectal, lung, breast, and ovarian cancer in which it is largely adopted. To date, there is no established role for maintenance therapy following first-line chemotherapy for advanced gastric cancer (GC). This review summarizes the current knowledge regarding maintenance strategies in advanced GC exploring cytotoxic agents, biologic agents and immunotherapy. We also critically review new issues to optimize randomized clinical trials for maintenance therapies and suggest clinical consideration to guide a personalized approach in daily clinical practice for this setting.